Functional design of a two-stage collapsible core for uPVC pipe fittings with an internal undercut - Chung, Yee Hian. (2008)
Undercuts are features of a plastic part which need to perform a particular function or to satisfy an artistic requirement. However, they prevent the removal of the plastic part from the mould. Undercuts are formed by special tools which increase the complexity of the mould and are tedious and expensive to design. Hence, the motivation to automate the design of moulding tools that form undercuts so as to reduce both the design cycle time and manufacturing costs. A survey among CAD-related works in the field of injection moulding did not reveal any automated tools which can form extensive internal undercuts. Extensive internal undercuts such as threads, grooves, etc. as well as local depressions can be formed by the collapsible core, which is a versatile moulding tool. This thesis discusses the design of collapsible cores which form circular 360° undercuts and the different mechanisms to actuate the core.